Schools, Household, Risk, and Gender: Determinants of Child Schooling in Ethiopia. - Chaudhury, N; Christiaensen, L; Asadullah, M (CSAE (University of Oxford), 2006)
Drawing upon data from Ethiopia, we highlight the relationship between investments in child schooling and key factors related to household characteristics, supply and quality of schooling, and income shocks. The unique contribution of this study stems from our examination of the effect of adverse income shocks on gender-differentiated child schooling outcomes. While there are several empirical studies that test the degree to which households are able to smooth consumption in response to a covariate shock, only few studies probe the gender-differentiated impacts of those shocks within the household. We find a strong bias against investments in female education in rural Ethiopia. Controlling for key supply and demand side factors such as household income, parental education, distance to and quality of schools, girls who reside in rural areas are almost 12 percent less likely to be enrolled in primary school compared to boys. Furthermore, while an adverse weather-induced crop shock has no discernable impact on the schooling of boys, the same adverse shock has a deleterious impact on both the probability of enrollment and completion of schooling for girls. Besides the impact of adverse income shocks on child schooling, we find that investment in child schooling is significantly influenced by positive education externalities with the household and community, availability and distance to schools, and quality of school infrastructure.